PEMBERIAN REWARD UNTUK MENINGKATKAN MOTIVASI BELAJAR BAHASA ARAB PESERTA DIDIK KELAS IV DI MIN 6 SINAR REZEKI JATI AGUNG LAMPUNG SELATAN - Siti Barokah, Siti Barokah; Nurul Aslamiyah; Ami Latifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low motivation of students in learning Arabic in grade IV of MIN 6 Sinar Rejeki Jati Agung, South Lampung. Low enthusiasm, lack of active participation, and weak internal motivation of students to understand the material indicate that the learning process has not been running optimally. To overcome these problems, teachers apply a reward strategy as a form of positive reinforcement that is expected to increase students' enthusiasm and motivation to learn. The purpose of this study is to explain the provision of rewards to increase the motivation to learn Arabic in grade IV students at MIN 6 Sinar Rezeki Jati Agung, South Lampung. This study uses a qualitative approach with the type of field research and descriptive methods to examine the application of reward provision in increasing the motivation to learn Arabic in grade IV students of MIN 6 Sinar Rejeki Jati Agung, South Lampung. Data collection techniques included direct observation during the learning process, in-depth interviews with the principal, Arabic language teachers, and students, and documentation related to learning activities. To test the validity of the data, this study employed source and technical triangulation techniques. The results showed that the implementation of rewards in Arabic language learning in fourth grade at MIN 6 Sinar Rejeki Jati Agung, South Lampung, had a significant positive impact on student learning motivation. Teacher rewards in the form of praise, simple gifts, symbolic awards, and additional credits increased student enthusiasm, activeness, and participation during learning activities.